QUANTITATIVE PARAMETERS OF NUCLEAR AND FREE CELL DNA IN NEWBORN BABIES WITH CLINICAL MANIFESTATIONS OF ADAPTATION DERANGEMENT IN EARLY NEONATAL PERIOD - V.V. Sofronov; N.O. Tuaeva; V.G. Vinter; V.A. Emikeeva; D.I. Shegurova; E.V. Mavrina ("Paediatrician" Publishers LLC, 2006)
In the paper were presented the results of an investigation of the nucleus area and metabolism DNA parameters (the level of nuclear DNA uptake, the level of a chromatin condensation and the concentration of plasma free cell DNA) in newborns with clinical manifestations of adaptation derangement (a perinatal CNS damage, an intrauterine pneumonia and a neonatal pneumopathy) in early neonatal period. In all cases the disorders of a DNA metabolism was obtained. However, the greatest divergence of all investigated parameters was founded in newborns with neonatal pneumo pathy. We made the assumption that lymphocyte apoptosis may be part of the reason for the origin of free cell DNA and we propose the possible mechanism of free cell DNA sharing in pathogenesis of derangement adaptation in neonatal period. Key words: free cell DNA, nuclear DNA, intrauterine pneumonia, pneumopathy.